Sistem Informasi Persediaan Bahan Baku pada Barbekoe Coffee Menggunakan Metode Buffer Stock dan FEFO - Agil, Mashuril; Triase, Triase (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Inventory information system is an important aspect of running a business, especially for Micro, Small and Medium Enterprises (MSMEs). Barbekoe Coffee is a Micro, Small and Medium Enterprise (MSME) in the city of Medan engaged in coffee shops (Coffeeshop). In carrying out its operations, Barbekoe Coffee still uses manual recording on a piece of paper on raw material inventory ranging from incoming raw materials, outgoing raw materials, raw material inventory, to ordering raw materials. This often causes problems ranging from damaged or lost records, repeated ordering of raw materials on the same raw materials and employees who often remove raw materials from the warehouse not in the order in which the raw materials enter. So often found raw materials in damaged and expired warehouses. The purpose of this study is to create and implement an appropriate and accurate inventory information system in order to minimize losses and optimize profits in the Barbekoe Coffee business. The methods used are Buffer Stock, First Expired First Out (FEFO), and Reorder Point. After testing, the system runs as expected. Barbekoe Coffee can implement precise and accurate inventory flows to increase profits and avoid losses due to damaged or expired raw materials.